Lymphatic Drainage-Promoting Effects by Engraftment of Artificial Lymphatic Vascular Tissue Based on Human Adipose Tissue-Derived Mesenchymal Stromal Cells in Mice - Asano, Yoshiya; Shimoda, Hiroshi; Okano, Daisuke; Matsusaki, Michiya; Akashi, Mitsuru (Journal of tissue engineering and regenerative medicine, 2023)
Regenerative medicine using lymphatic vascular engineering is a promising approach for treating lymphedema. However, its development lags behind that of artificial blood vascular tissue for ischemic diseases. In this study, we constructed artificial 3D lymphatic vascular tissue, termed ASCLT, by co-cultivation of ECM-nanofilm-coated human adipose tissue-derived mesenchymal stromal cells (hASCs) and human dermal lymphatic endothelial cells (HDLECs). The effect of hASCs in lymphatic vessel network formation was evaluated by comparison with the tissue based on fibroblasts, termed FbLT. Our results showed that the density of lymphatic vascular network in ASCLT was higher than that in FbLT, demonstrating a promoting effect of hASCs on lymphatic vascular formation. This result was also supported by higher levels of lymphangiogenesis-promoting factors, such as bFGF, HGF, and VEGF-A in ASCLT than in FbLT. To evaluate the therapeutic effects, FbLTs and ASCLTs were subcutaneously transplanted to mouse hindlimb lymphatic drainage interruption models by removal of popliteal and subiliac lymph nodes. Despite the restricted engraftment of lymphatic vessels, ASCLT promoted regeneration of irregular and diverse lymphatic drainage in the skin, as visualized by indocyanine green imaging. Moreover, transplantation of ASCLT to the popliteal lymph node resection area also resulted in lymphatic drainage regeneration. Histological analysis of the generated drainage visualized by FITC-dextran injection revealed that the drainage was localized in the subcutaneous area shallower than the dermal muscle. These findings demonstrate that ASCLT promotes lymphatic drainage in vivo and that hASCs can serve as an autologous source for treatment of secondary lymphedema by tissue engineering.